On performance evaluation of OFDM-BPSK and -QPSK over Nakagami-m fading channel with EGC technique. (1st January 2013) - Sood, Neetu; Sharma, Ajay K.; Uddin, Moin
Diversity techniques are known to reduce the deleterious effect of fading and largely deployed in wireless communication. This paper aims at exploring the strengths of equal gain combining (EGC) diversity scheme by evaluating the error performance analysis of OFDM-BPSK and -QPSK-based system in the presence of Nakagami-m fading channels. Previous work carried to evaluate the performance analysis of OFDM system in Nakagami-m fading channel has yield an optimum value of fading parameter m. Here, the extension of same work has been presented by deploying the EGC scheme. Simulated results clearly reveal that the use of EGC schemes improves the system performance by manifolds.